2015
DOI: 10.1074/jbc.m115.662098
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ascorbate Prevents Endothelial Barrier Permeabilization by Thrombin

Abstract: Background: Vitamin C (ascorbate) promotes endothelial barrier stability during inflammation. Results: Ascorbate prevents inflammatory decreases in cAMP. Conclusion: cAMP preserves the cortical actin cytoskeleton and prevents stress fiber formation. Significance: Dietary vitamin C may promote vascular integrity in patients with inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
0
22
2
Order By: Relevance
“…The cause of thrombin-induced endothelial hyperpermeability involved activation of the small GTPase RhoA and Rho kinase, which increased the phosphorylation of MLC. In addition, Parker et al [43] demonstrated that thrombin induced endothelial barrier destabilization, at least partly, by inhibiting the activation of Rap1 and Rac1 and increasing the phosphorylation and distribution of VE-cadherin, the phosphorylation of MLC, and actin polymerization. Consistent with the results of previous studies, we observed that after endothelial cells were exposed to 0.5 mmol/L OA, the expression of pMLC was increased in the AT III siRNA group compared with that in the control siRNA group.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of thrombin-induced endothelial hyperpermeability involved activation of the small GTPase RhoA and Rho kinase, which increased the phosphorylation of MLC. In addition, Parker et al [43] demonstrated that thrombin induced endothelial barrier destabilization, at least partly, by inhibiting the activation of Rap1 and Rac1 and increasing the phosphorylation and distribution of VE-cadherin, the phosphorylation of MLC, and actin polymerization. Consistent with the results of previous studies, we observed that after endothelial cells were exposed to 0.5 mmol/L OA, the expression of pMLC was increased in the AT III siRNA group compared with that in the control siRNA group.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the source of oxidative stress, it is clear that increasing cellular antioxidant capacity might be beneficial in decreasing VEGF-induced hyperpermeability. In this regard, we have shown that vitamin C, or ascorbic acid, prevents endothelial barrier leakage due to oxidized low density lipoprotein [14] and more recently due to thrombin [15]. Although ascorbate is considered an important cellular antioxidant, in both basal [16] and thrombin-activated cells [15], the vitamin enhanced the function of eNOS to generate nitric oxide (NO).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have shown that vitamin C, or ascorbic acid, prevents endothelial barrier leakage due to oxidized low density lipoprotein [14] and more recently due to thrombin [15]. Although ascorbate is considered an important cellular antioxidant, in both basal [16] and thrombin-activated cells [15], the vitamin enhanced the function of eNOS to generate nitric oxide (NO). It is known from a previous study that ascorbate promotes NO generation by recycling the crucial eNOS co-factor tetrahydrobiopterin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate loading of HUVECs also completely prevented the endothelial barrier leak caused by short-term treatment with the inflammatory agent thrombin [111]. In that study, ascorbate acting through NO increased cyclic GMP and prevented the thrombin-induced decrease in cyclic AMP.…”
Section: Ascorbate Functions That May Decrease Pericyte Loss and Endomentioning
confidence: 95%